2021
DOI: 10.1021/acs.jpcb.1c07782
|View full text |Cite
|
Sign up to set email alerts
|

How Temperature, Pressure, and Salt Concentration Affect Correlations in LiTFSI/EMIM-TFSI Electrolytes: A Molecular Dynamics Study

Abstract: Classical polarizable molecular dynamics simulations have been performed for LiTFSI solutions in the EMIM-TFSI ionic liquid. Different temperature or pressure values and salt concentrations have been examined. The structure and dynamics of the solvation shell of Li+ cations, diffusion coefficients of ions, conductivities of the electrolytes, and correlations between motions of ions have been analyzed. The results indicated that regardless of the conditions, significant correlations are present in all systems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
4
1
Order By: Relevance
“…From the evidence examined above it is clear that (1) our data do not support Suarez' claims: the volumes of activation for the anion and cation self-diffusion coefficients do not differ significantly, as shown in Fig. 5 and Table 7, which includes activation volumes derived for all the ionic liquids in our high pressure works: the recent molecular dynamics simulations of Kubisiak et al 45 are consistent with this result; (2) the pressure dependence of the D si is similar to that for [BMIM][Tf 2 N] and [HMIM][Tf 2 N]; (3) all three ionic liquids yield typical Stokes-Einstein-Sutherland diffusion-viscosity plots with overlaid isotherms and isobars collapsed onto a single line and with fractional exponents between 0.9 and 1, similar to other ionic and non-associated molecular liquids, whereas the Suarez data are inconsistent, with different slopes for the high-pressure isotherms and atmospheric pressure isobars; (4) the present data conform to thermodynamic or density scaling, with very similar scaling constants for the self-diffusion coefficients and the viscosity, again consistent with results for other ionic liquids. So the conclusion must be that there is nothing significantly different in the effect of pressure on the selfdiffusion of the ions in [EMIM][Tf 2 N] to support a different ''slithering'' mechanism for the [Tf 2 N] À ([TFSA] À ) ion in this ionic liquid distinct from that of other cations or anions or in [Tf 2 N] À salts with larger 1-alkyl-3-methylimidazolium cations.…”
Section: Thermodynamic Scalingcontrasting
confidence: 61%
“…From the evidence examined above it is clear that (1) our data do not support Suarez' claims: the volumes of activation for the anion and cation self-diffusion coefficients do not differ significantly, as shown in Fig. 5 and Table 7, which includes activation volumes derived for all the ionic liquids in our high pressure works: the recent molecular dynamics simulations of Kubisiak et al 45 are consistent with this result; (2) the pressure dependence of the D si is similar to that for [BMIM][Tf 2 N] and [HMIM][Tf 2 N]; (3) all three ionic liquids yield typical Stokes-Einstein-Sutherland diffusion-viscosity plots with overlaid isotherms and isobars collapsed onto a single line and with fractional exponents between 0.9 and 1, similar to other ionic and non-associated molecular liquids, whereas the Suarez data are inconsistent, with different slopes for the high-pressure isotherms and atmospheric pressure isobars; (4) the present data conform to thermodynamic or density scaling, with very similar scaling constants for the self-diffusion coefficients and the viscosity, again consistent with results for other ionic liquids. So the conclusion must be that there is nothing significantly different in the effect of pressure on the selfdiffusion of the ions in [EMIM][Tf 2 N] to support a different ''slithering'' mechanism for the [Tf 2 N] À ([TFSA] À ) ion in this ionic liquid distinct from that of other cations or anions or in [Tf 2 N] À salts with larger 1-alkyl-3-methylimidazolium cations.…”
Section: Thermodynamic Scalingcontrasting
confidence: 61%
“…Nevertheless, others observed a trend of anions replacing solvents from the vicinity of cations with increasing temperatures (Figure b). It was also reported that the association between cations and anions was hardly modified regardless of the temperature . As their electrolyte recipes differ from each other, it is difficult to draw compelling conclusions on the influences of temperatures on electrolyte structures.…”
Section: Electrolyte Microstructuresmentioning
confidence: 99%
“…It was also reported that the association between cations and anions was hardly modified regardless of the temperature. 306 As their electrolyte recipes differ from each other, it is difficult to draw compelling conclusions on the influences of temperatures on electrolyte structures. It is also likely that the temperatures do affect microstructures to different extents depending on specific electrolyte components, and further investigations are necessary to reveal the general principles.…”
mentioning
confidence: 99%
“…26−30 The objective of this research is to assess the two most important macroscopic properties, density and dynamic viscosity, of the mixtures of Li-salt, water, and four structurally different room-temperature ionic liquids (RTILs). 31 The effect of temperature and Li-salt concentration on the physical properties of the systems was investigated to probe the microstructural environment and the changes in the physical forces of interactions within the ternary electrolytic mixtures constituting ions and water molecules. 32 In order to fully utilize these (RTIL + water + salt) systems for industrial and scholarly purposes, it is anticipated that understanding the temperature as well as the composition interdependence of density and dynamic viscosity of these systems will be of utmost importance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The objective of this research is to assess the two most important macroscopic properties, density and dynamic viscosity, of the mixtures of Li-salt, water, and four structurally different room-temperature ionic liquids (RTILs) . The effect of temperature and Li-salt concentration on the physical properties of the systems was investigated to probe the microstructural environment and the changes in the physical forces of interactions within the ternary electrolytic mixtures constituting ions and water molecules .…”
Section: Introductionmentioning
confidence: 99%